Immunometabolic Network Interactions of the Kynurenine Pathway in Cutaneous Malignant Melanoma - Rad Pour, Soudabeh; Morikawa, Hiromasa; Kiani, Narsis A.; Gomez-Cabrero, David; Hayes, Alistair; Zheng, Xiaozhong; Pernemalm, Maria; Lehtiö, Janne; Mole, Damian J.; Hansson, Johan; Eriksson, Hanna; Tegnér, Jesper (Frontiers in Oncology, 2020)
Dysregulation of the kynurenine pathway has been regarded as a mechanism of tumour immune escape by the enzymatic activity of indoleamine 2, 3 dioxygenase and kynurenine production. However, the immune modulatory properties of other kynurenine metabolites such as kynurenic acid, 3-hydroxykynurenine, and anthranilic acid are poorly understood. In this study, plasma from patients diagnosed with metastatic cutaneous malignant melanoma (CMM) was sampled before (PRE) and during treatment (TRM) with inhibitors of mitogen-activated protein kinase pathway (MAPKIs). Immuno-oncology related protein profile and kynurenine metabolites were analyzed by proximity extension assay (PEA) and LC/MS-MS, respectively. Correlation network analyses of data derived from PEA and LC/MS-MS identified a set of proteins that modulate the differentiation of Th1 cells, which is linked to 3-hydroxykynurenine levels. Moreover, MAPKIs treatments are associated with changes in 3-hydroxykynurenine and 3hydroxyanthranilic acid (3HAA) concentrations and led to higher “CXCL11”, and “KLRD1” expression, involved in T and NK cells activation. These findings imply that the kynurenine pathway is pathologically relevant in patients with CMM.